Birth order and mental deficiency in institutionalized retardates - Cleland, Charles C.; Phillips, Beeman N. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Altus’ review of the literature (Science, 1966) on the relation of birth order to eminence, intelligence, college attendance and other social parameters was generally consistent in finding first-borns to be over-represented. Complementary evidence at the lower end of the intellectual continuum following an extensive review of the mental deficiency literature appeared non-existent. To partially fill this lacuna, an effort was made to provide evidence concerning the relation between ordinal position of birth and mental deficiency. Data were obtained for 4,398 institutionalized retardates. First-borns with siblings were compared with later borns on the variables of family size, sex, ethnicity, intelligence, and socioeconomic status, yielding significant differences between observed and expected frequency distributions on groupings of family size, intelligence, and father’s educational level. Only-children were studied separately; the distribution being significantly different from expectation on the variables of ethnicity, intelligence, and father’s educational attainment. Two methodological issues relevant to birth order studies are considered and implications are discussed in terms of family interaction patterns.